Reinventing the entrepreneur - Tribby, MaryEllen
Introducing a million-dollar business model that you can do from home, on the road, or in your spare time Mary Ellen Tribby, founder of Working Moms Only, has created and perfected a business model that is 500% more profitable than blogging, that you can do from home, from an office, or from anywhere in the world, that's easy to learn, and extremely profitable. With it, Mary Ellen has made millions through her various own businesses and her clients, and now you can too. It's called The Inbox Magazine (The iMag for short) and regardless of the size of your staff from one to one hundred or whether you spend ten or forty hours a week working at it, this revolutionary approach to running a business is your ticket to success and financial independence